A kinematics analysis of giant swing backward and double salto backward stretched dismount in Jinnan Yao 's uneven bars - Zhong, L.; Zhou, J.; Wang, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Using 3D camera analytic method, the paper tests Jinnan Yao`s (who won the gold medal in the female uneven bars final of the 45th World Gymnastics Championship in October 11th, 2014) technical movements of giant swing backward and double salto backward stretched dismount and make a kinematics analysis of the complete movements. The purpose of this study was to reveal the kinematic rules and technical features of the movements, in order to provide references of technical training for athletes. The results indicated that better performance was demonstrated if gymnast could increase the height of salto suspension,so that increase the flight time, in order to prepare landing.